Structural characterization and in vitro hepatoprotective activity of polysaccharide from pine nut (Pinus koraiensis Sieb. et Zucc.). (1st November 2019) - Qu, Hang; Gao, Xin; Zhao, Hai-Tian; Wang, Zhen-Yu; Yi, Juan-Juan
Highlights: A new polysaccharide is isolated from Pinus koraiensis Sieb. et Zucc. pine nuts. The compositions and structural characterization of PNP40c-1 are identified. PNP40c-1 shows hepatoprotective effect against CCl4 -induced liver damage in vitro . Abstract: A new purified polysaccharide (PNP40c-1) with a molecular weight of 2.06 × 10 5 Da was obtained from pine nuts ( Pinus koraiensis Sieb. et Zucc. ). Structural analysis indicated that PNP40c-1 is a homogeneous heteropolysaccharide composed of arabinose, rhamnose and glucose in a molar ratio of 2.98:1.00:0.52. The major backbone consisted of →3, 4)- α -l -Ara p (1→, →4)- α -l -Ara p 3Me(1→, →3)- α -l -Rha p (1→ and →6)- β -d -Glc p (1→, and the side chain is β -d -Glc p -(1→ linked at C4-position of →3, 4)- α -l -Ara p (1→. In addition, the hepatoprotective effect of PNP40c-1 was investigated by human hepatocyte cell line L02 treated with carbon tetrachloride (CCl4 ). Results suggested that PNP40c-1 could protect L02 cells from CCl4 -induced damage by enhancing the activities of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), increasing the level of non-enzymatic antioxidant glutathione (GSH), suppressing lipid perioxidation and further reducing the leakage of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Hence, PNP40c-1 could be a promising functional food to serve as hepatoprotective agent.